Challenges to injury control and safety in Africa. (1st March 2011) - Solagberu, B; El-Sayed, H; Mtonga, R; Nakitto, M
Abstract : Problem under study: There are limited achievements for injury control in Africa, despite the growing burden of injuries in the continent. This deterioration in the situation is mostly dues to demographic changes, population increases without commensurate infrastructure, failure to reach a critical mass of researchers, and poorly funded institutions working for injury control and safety promotion, which reflects the little national political support for these important issues. Objectives: To showcase injury research and prevention successes and challenges in Africa. To provide an African Injury Control marketplace where the following transactions can take place: exchange of funding information, sharing of proposals, recruitment of partners for new and on-going research and or intervention projects. To develop strategies to attract more resources and researchers for injury control in Africa. Methods and approach: – Presentations of representatives of the different African regions for successes and challenges facing injury control in their regions. – Develop and discuss ideas for plans for future efforts for injury control and safety promotion in the continent. – Question/discuss. – Debate of proposed ideas. Expected results: This round table will help in charting out plan to maximise the benefits from research already done, networks formed, and interventions executed or planned. Based on the present situation analysis new opportunities for forging ahead, and for maximising our pressure on policy makers will be captured and planned in the various African countries to promote the national and moreover continental programmes for injury control and safety promotion.